Cognitive radio frequency sense solution based on tracing location - WANG Yi-ming; ZHOU Liu-lei (Tongxin xuebao)
A frequency sense solution based on the double-station cooperation and multi-hop tracing localization was presented for resolving the hidden and exposed problems in the dynamic spectrum resource management so as to improve reliability and efficiency of the frequency sense and increase the utilization of spectrum.In this scheme,the secondary user could detect primary user’s existing by an improved centroid localization algorithm cooperated with a known position user.The detailed steps were proposed,the simulation results were discussed and the performance of the tracing localization was analyzed.